Citizen Coherence and Cultivated Cleanliness: Using Technology-Induced Social Norms to Strengthen Sustainable Household Bonds - Siepelmeyer, Henrik; Otterbring, Tobias (Frontiers in Sustainability, 2022)
Social identity and social capital are critical to human well-being and sustainable development. However, existing research on sustainable behavior typically treats these factors merely as taken-for-granted preconditions to environmental protection. This paper argues that they can also be direct outcomes of environment-oriented efforts, thus becoming drivers of sustainable societies. As part of a larger research project on household recycling and waste behavior, the authors assess and compare perceived social identity and social capital of residents in a multi-family residential dwelling in Sweden before (N = 66) and after (N = 18) exposure to a social norm-based intervention delivered through a smartphone app. Reported levels of social identity and social capital were higher after (vs. before) the intervention, both compared to participants’ own previous measurement and a control group. Together, the current research offers a novel perspective on technology-enabled social norms. Specifically, such norms may not only create sustainable responses immediately, but may also play a pivotal role in shaping more sustainable communities in the long run. Future studies are needed to elucidate the specific psychological mechanisms driving the observed effects and shed further light on whether, when, and why social norms may foster sustainable responses with a clear social connotation.